The Portfolio, the Log, and Dictation: Teaching Strategies to Improve the Writing Process - Ugalde Villalobos, María Eugenia (2020)
This essay presents strategies to improve the writing process with the use of log books, porftolios, and dictation combined with a hybrid or blended–learning methodology in the course of Communication and Writing of the School of Professional Secretariat at Universidad Nacional. In addition, it emphasizes that punctuation and spelling improve greatly when students put into practice the aforementioned tools since those are the contents that students fail the most in the writing process. In conclusion, the key to improving writing is the feedback given among the teacher – students, face-to-face classes – virtual classes and revision – correction.